Analytical Behavior of Multi-Storied Building with Base Isolation Subjected to Earthquake Loading - Nasir Ghadhban AL-Maliki, Hadi (Journal of Engineering and Sustainable Development, 2013)
This study involves analysis of multi-storied building to explain the behavior under seismic earthquake loading in two cases, (i.e. with or without base isolation system). The buildings of the same properties of five stories were analyzed consist of steel parts (beams and columns) with reinforced concrete slabs and isolated system supported provided by fixed or Nllink supports. The responses of building at each case are determined to evaluate the base isolation systems that used under static and dynamic (earthquake) loading. The analysis was done by used the finite elements procedure provided by SAP2000 version14 program. In this studied covers concept, Analysis, working and other aspects of using isolator or not with building and effect when using (isolator) in reduction translation, base shear and moment due to ability to dispersion the energy.From the analysis results it was found that when using rubber bearing pad to isolate the base building gives reduction the values of absolute maximum acceleration of basement in the isolated building by about 90% (i.e. decrease inertia forces)